2013
DOI: 10.1515/form.2011.123
|View full text |Cite
|
Sign up to set email alerts
|

Imprecise probabilities, bets and functional analytic methods in Łukasiewicz logic

Abstract: In his foundation of probability theory, Bruno de Finetti devised a betting scheme where a bookmaker offers bets on the outcome of events φ occurring in the future. He introduced a criterion for coherent bookmaking, and showed that coherent betting odds are given by some probability distribution. While de Finetti dealt with yes-no events and boolean propositional logic, Mundici generalized the theory to the continuous spectrum events formalized within Lukasiewicz logic.Both de Finetti and Mundici assume that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…½0; 1 is an MV-seminorm then define u :¼ fs : A ! ½0; 1js ug: As in Lemma 4.2 of Fedel et al (2012), the maps u 7 ! u and X 7 !…”
Section: Example 21mentioning
confidence: 98%
See 2 more Smart Citations
“…½0; 1 is an MV-seminorm then define u :¼ fs : A ! ½0; 1js ug: As in Lemma 4.2 of Fedel et al (2012), the maps u 7 ! u and X 7 !…”
Section: Example 21mentioning
confidence: 98%
“…We give in Remark 2.4 a probabilistic interpretation of MVseminorms as 'imprecise (upper) probabilities'. One can see Fedel et al (2012) for an analysis of 'imprecise probabilities' in Łukasiewicz logic.…”
Section: Definition 13 (Mv-seminorm) Ifmentioning
confidence: 99%
See 1 more Smart Citation
“…We begin by recalling a characterisation of coherence as avoiding inadmissible bets given in [6] (the terminology "bad bet" was used there.) Definition 5.…”
Section: Fuzzy Imprecise Probabilities Over the Hyperrealsmentioning
confidence: 99%
“…In [6] it is shown that an assessment of upper probability avoids inadmissible bets iff it can be extended to an upper prevision. The result was shown first, although in a different setting, by Walley in [12].…”
Section: Fuzzy Imprecise Probabilities Over the Hyperrealsmentioning
confidence: 99%